(untitled) (International Journal of Innovative Research in Engineering & Management, 2023)
This chapter examines a variety of milk processing methods that are either new or emerging. Thermal therapies have traditionally been used in the dairy sector since they are effective in inactivating bacteria as well as enzymes. Several of these heat treatments, however, cause significant chemical changes in the food, leading to variations not only in the sensory aspects of the meal, but also in its nutritional content. Due to these constraints, the dairy sector is looking for new ways to enhance existing products and create new ones which are high-quality as well as consistent. The bulk of these cutting-edge technologies aren’t brand new; they’ve been tried and proven in the food industry for decades. Their resurgence has lately been fueled by technological and scientific advancements, as well as consumer desires for minimally processed meals. The authors have tried to gather the most researched technologies that are alternatives to traditional thermal treatments in this chapter. The following subjects are covered: general issues, impacts on microbes and enzymes, as well as chemical and sensory changes. Despite the large number of studies that have been completed, additional study is required to confirm the efficacy of these technologies and, as a result, to find serious alternatives to conventional therapies.